Smart agriculture’s IOT application for sustainable plant growth - Chong, Zi Jian (2024)

(untitled)
Since the pace of life is becoming faster, many people may not remember or lazy to take care of their plants. Furthermore, one of the elements affecting the plant's growth process is the weather. It may lead to the process of photosynthesis not able to progress and affect the temperature and humidity of the environment of plants. To overcome this problem, the smart plant monitoring system is promoted in this project. It can help the user to monitor the condition of the plant automatically. Then, this can prevent the case of overwatering or no watering even if the soil is dry. Next, the monitoring also includes temperature control which will decrease the temperature of the environment of the plant if the temperature of the plant environment is higher than the pre-setting temperature. To ensure the process of photosynthesis can be conducted, the monitoring system also will determine the intensity of light in the surrounding of the plant and the sunlight will be replace by full spectrum of light if the intensity of light in the plant environment is low or dark. Through this monitoring system, it can help the user to take care of their plants in a healthy growing environment